2021
DOI: 10.1111/jfpp.16215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the substitution of common flours for gluten‐free flours in cookies

Abstract: Sensory quality is very important to determine the acceptance of food by consumers, and it is essential to identify the sensory attributes that contribute to food acceptability. This paper aimed to identify the attributes that contribute to the sensory acceptance of cookies containing rice, sorghum, and teff flour. The formulations were subjected to sensory descriptive analysis (Flash Profile) to describe the cookie samples. The substitution of wheat flour for sorghum and teff flour did not affect the acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Texture profile analysis (TPA) was performed using a TA-XT plus texture analyzer (Stable Micro Systems Ltd., Surrey, UK) with a 36 mm diameter cylinder probe P/36R, according to the method described by de Castro et al [ 26 ]. The bread was cut into pieces with a thickness of 5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Texture profile analysis (TPA) was performed using a TA-XT plus texture analyzer (Stable Micro Systems Ltd., Surrey, UK) with a 36 mm diameter cylinder probe P/36R, according to the method described by de Castro et al [ 26 ]. The bread was cut into pieces with a thickness of 5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…It could be concluded that the CC powder improved the sensorial quality of cookie incorporated with FS flour. de Castro et al (2022) reported the use of teff flour with rice and sorghum flours improved the sensorial acceptance of cookies. The teff flour was darker compared to other flours.…”
Section: Discussionmentioning
confidence: 99%
“…Composite flours can be used in the cookie production to improve the nutritional and functional values of cookies. The replacement of wheat flour with flours from cereals such as corn, rice, teff, and sorghum and legumes such as chickpea and kidney bean have been investigated (de Castro et al, 2022; Homem et al, 2022; Sibian & Riar, 2020, 2021, Zoghi et al, 2021). Moreover, the use of various seeds including quinoa and chia seeds (Goyat et al, 2018; Lucini Mas et al, 2020), flaxseed (Rajiv et al, 2012), hemp seed (Ertaş & Aslan, 2020), okra seed (Hu et al, 2020), and grape seed (Acun & Gül, 2014) have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The texture of the biscuit dough and biscuit were measured by a Texture Analyzer (TA-XT plus, Stable Micro Systems Ltd., Surrey, UK) equipped with P36R probe to 25% of the original sample height with a test speed of 2 mm/s under a Texture Profile Analysis (TPA) model. The assessed parameters were hardness, springiness, cohesiveness, gumminess and resilience for the dough and hardness, cohesiveness, chewiness and resilience for the biscuit, respectively [ 21 ].…”
Section: Methodsmentioning
confidence: 99%